IMPLEMENTATION OF EMOTIONAL AND SPIRITUAL QUOTIENT IN ISLAMIC RELIGIOUS EDUCATION IN SMA NEGERI 20 PANGKEP - Ruhul Yusuf; Muhammad Yaumi; Muhammad Khalifah Mustami (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstrack: The purpose of this study is to determine the implementation of emotional and spiritual quotient in learning Islamic religious education at SMA Negeri 20 Pangkep. This type of research is descriptive qualitative with a phenomenological and pedagogical-psychological approach. The location of this research is SMA Negeri 20 Pangkep in class X. The data source is the primary data of all Islamic religious education teachers, while the secondary data is RPP documents related to the object under study. Data obtained through observation, interviews and documentation, then data processing using the Milles and Huberman model (data reduction, data presentation and conclusion) with analysis using triangulation to ensure data validity against the focus under study. The results of this study indicate that the implementation of emotional and spiritual quotient in Islamic religious education learning at SMA Negeri 20 Pangkep is an Islamic religious education learning activity in which several emotional and spiritual quotient indicators are integrated, including; managing self-emotion, empathy, building relationships (relations), meaning and high self-awareness. This concept is combined by the Islamic religious education teacher at SMA Negeri 20 Pangkep in implementing Emotional and Spiritual quotient.